Fish oil supplementation reduces markers of oxidative stress but not muscle soreness after eccentric exercise - Gray, P.; Chappell, A.; McE Jenkinson, A.; Thies, F.; Gray, S. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Due to the potential anti-inflammatory properties of fish-derived long chain n-3 fatty acids, it has been sug- gested that athletes should regularly consume fish oils—although evidence in support of this recommendation is not clear. While fish oils can positively modulate immune function, it remains possible that, due to their high number of double bonds, there may be concurrent increases in lipid peroxidation. The current study aims to investigate the effect of fish oil supplementation on exercise-induced markers of oxidative stress and muscle damage. Twenty males underwent a 6-week double-blind randomized placebo-controlled supplementation trial involving two groups (fish oil or placebo). After supplementation, participants undertook 200 repetitions of eccentric knee contractions. Blood samples were taken presupplementation, postsupplementation, imme- diately, 24, 48, and 72 hr postexercise and muscle soreness/maximal voluntary contraction (MVC) assessed. There were no differences in creatine kinase, protein carbonyls, endogenous DNA damage, muscle soreness or MVC between groups. Plasma thiobarbituric acid reactive substances (TBARS) were lower (p < .05) at 48 and 72 hr post exercise and H2O2 stimulated DNA damage was lower (p < .05) immediately postexercise in the fish oil, compared with the control group. The current study demonstrates that fish oil supplementation reduces selected markers of oxidative stress after a single bout of eccentric exercise.